Secure Signature Schemes Based on Interactive Protocols - Cramer, Ronald; Damgård, Ivan B. (BRICS Report Series, 1994)
A method is proposed for constructing from interactive protocols digital signature schemes secure against adaptively chosen message attacks. Our main result is that practical secure signature schemes can now also be based on computationally difficult problems other than factoring, such as the discrete logarithm problem.